Pembangunan sistem penilaian prestasi berdasarkan teknik skala perkadaran bergrafik - Hussin, Noryanti (2007)
Performance appraisal is an important and effective management mechanism to control and ensure the employee’s performance in parallel with organizational objective. There are several techniques can be used for performance appraisal in organization. Based on research about performance appraisal techniques, Graphic Rating Scales Techniques is chosen to be used in developing on Performance Appraisal System of Kumpulan Pendidikan YPJ. Methodology used in developing the system is Phase Development Based Methodology. The analysis and design technique is based on the Object- Oriented modeling. For the implementation phase, the programming language that has been used is PHP and MYSQL as a database.